2015
DOI: 10.1177/230949901502300222
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Operative Fractures in Cementless Bipolar Hemiarthroplasty

Abstract: Purpose. To compare patients with or without intra-operative fracture during cementless bipolar hemiarthroplasty. Methods. Records of 76 men and 202 women who underwent cementless bipolar hemiarthroplasty for femoral neck fractures were reviewed. Patients with and without intra-operative fractures and patients with different types of intra-operative fractures were compared. Results. Two men and 22 women aged 62 to 93 (mean, 80) years sustained intra-operative fractures at the lesser trochanter (n=18), the grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…In randomized controlled trials, Parker et al [9] and Taylor et al [19] have shown the fracture incidence to be significantly higher with uncemented hemiarthroplasty. The overall fracture rate of 7.1%, as well as the isolated fracture rate of 7.4% for uncemented arthroplasty as determined by this study, was consistent with the current literature [20, 21], especially when considering that 87.5% of procedures were cementless.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In randomized controlled trials, Parker et al [9] and Taylor et al [19] have shown the fracture incidence to be significantly higher with uncemented hemiarthroplasty. The overall fracture rate of 7.1%, as well as the isolated fracture rate of 7.4% for uncemented arthroplasty as determined by this study, was consistent with the current literature [20, 21], especially when considering that 87.5% of procedures were cementless.…”
Section: Discussionsupporting
confidence: 91%
“…This homogenous study population allowed us to retrospectively focus on risk factors in a widely unbiased fashion. To our knowledge, this is a study design, which has been adopted by only two other studies [20, 21]. Both studies used smaller population sizes (278 and 271, respectively) as well as heterogeneity of implant types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall incidence of IPF in our study was 8.6% (22 of 257), this finding is consistent with current literature 12 , 19 . Furthermore, the incidence of IPF in the Corail group was 12.2%, while the incidence of IPF in the Austin-Moore group was 4.2%, this difference is statistically significant ( p = 0.025).…”
Section: Discussionsupporting
confidence: 93%